GOVERNMENT'S NEW POLICY ON THE ARRANGEMENTS OF PARTICIPATING INTEREST - Yulianingsih, Indra; Algasahri, M. Ridwan Yusuf (TRUNOJOYO LAW REVIEW, 2020)
The Oil and Gas Ministerial Regulation Number 37 of 2016 concerning Provisions for a 10% (ten percent) "Participating Interest" offer in the Oil and Gas Working Area has the aim of increasing the participation of district local governments through ownership of "participating interest". For this reason, this research is needed on the arrangement of "Participating Interest" in the management of Oil and Gas in Indonesia, constraints on implementing "Participating Interest" in the management of Oil and Gas in Sampang Regency and new policies to resolve problems regarding "Participating Interest".The research method used is Applied Legal Research, using statute, case approach, and a conceptual approach. The result of this research is that the implementation of the Regulation of the Minister of Energy and Mineral Resources regarding the distribution of the 10% profit sharing in Sampang Regency has not been implemented. Therefore, a review of the ESDM Ministerial Regulation must be conducted regarding the provision of PI through BUMD and the participation of the private sector